Are active and passive smoking associated with cardiometabolic risk factors in adolescents? The CASPIAN-III Study. (2nd July 2016) - Kelishadi, Roya; Noori, Atefeh; Qorbani, Mostafa; Rahimzadeh, Shadi; Djalalinia, Shirin; Shafiee, Gita; Motlagh, Mohammad Esmaeil; Ardalan, Gelayol; Ansari, Hossein; Asayesh, Hamid; Ahadi, Zeinab; Heshmat, Ramin
Abstract : Background: Smoking is an important risky behavior in adolescents worldwide. Active and passive smoking have adverse health effects at public and individual levels. Objective: This study aimed to evaluate the association of active and passive smoking with cardiometabolic risk factors in a national sample of Iranian adolescents. Methods: Participants consisted of 5625 students, aged 10–18 years, studied in the third survey of a national school-based surveillance system. Participants were classified into three groups based on smoking pattern: active smoker, passive smoker, and exposure to smoke (active or passive or both of them). Considering the Adult Treatment Panel III criteria modified for the paediatric age group, metabolic syndrome (MetS) was defined as the co-existence of three out of five components of abdominal obesity, elevated blood pressure, elevated fasting plasma glucose, high serum triglycerides, and depressed high-density cholesterol (HDL-C) levels. Results: The mean (SD) age of participants was 14.7 (2.4) years. Mean level of HDL-C was significantly lower in all types of smoking compared to non-smokers. Low HDL-C and MetS had significant association with active smoking (OR 2.10, 95% CI 1.33–3.31 and OR 5.24, 95% CI 2.41–11.37), passive smoking (OR 1.19, 95% CI 1.01–1.43 and OR 1.79, 95% CI 1.09–2.96), and smoking exposure (OR 1.20, 95% CI 1.01–1.43 and OR 2.02, 95% CI 1.22–3.31), respectively. Conclusion: This study confirms that both smoking and exposure to smoke are associated with an increased risk of MetS and some of the cardiometabolic risk factors in adolescents. Preventive measures against passive smoking should be considered as a health priority in the paediatric age groups.